2015
DOI: 10.1007/s10096-015-2501-z
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile infection in patients with liver disease: a review

Abstract: Over the past two decades, there has been a dramatic worldwide increase in both the incidence and severity of Clostridium difficile infection (CDI). Paralleling the increased incidence of CDI in the general population, there has been increased interest in CDI among patients with liver disease, particularly in those with liver cirrhosis and post liver transplantation. MEDLINE and several other electronic databases from January 1995 to December 2014 were searched in order to identify potentially relevant literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 117 publications
(212 reference statements)
0
31
0
Order By: Relevance
“…For CDI specifically, CLD associated immune dysfunction leads to an immunocompromised state due to altered immune response and dysbiosis of gut microbiota. [6, 7] Previous studies have shown that CDI in patients with CLD results in increases mortality, morbidity, and cost. [6, 11] This study confirms and extends these findings by demonstrating that mortality and cost are increased significantly in this patient population compared to patients with CDI without CLD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For CDI specifically, CLD associated immune dysfunction leads to an immunocompromised state due to altered immune response and dysbiosis of gut microbiota. [6, 7] Previous studies have shown that CDI in patients with CLD results in increases mortality, morbidity, and cost. [6, 11] This study confirms and extends these findings by demonstrating that mortality and cost are increased significantly in this patient population compared to patients with CDI without CLD.…”
Section: Discussionmentioning
confidence: 99%
“…[6, 7] Previous studies have shown that CDI in patients with CLD results in increases mortality, morbidity, and cost. [6, 11] This study confirms and extends these findings by demonstrating that mortality and cost are increased significantly in this patient population compared to patients with CDI without CLD. The observed worse outcomes in patients with CLD are likely due to a higher severity of underlying illness in this patient population compared to other chronically ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. difficile is a spore-forming, anaerobic, gram-positive bacillus bacterium which causes a wide spectrum of illnesses from asymptomatic colonization or mild diarrhea to fulminant disease characterized by toxic megacolon, sepsis, pseudomembranous colitis and death (2-4). C. difficile infection is less common in children than adults, but its prevalence is increasing in children (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cirrhosis are also at increased risk for Clostridium difficile infection (CDI), with a rising incidence that has run in parallel to the general population over the last two decades. CDI significantly impacts patient outcomes, including increased length of stay and decreased survival among patients with cirrhosis . A recent retrospective study of CDI among LT recipients showed that a large proportion of CDI occurred within 1 week post‐LT and was associated with lower overall survival .…”
Section: Clostridium Difficile Infectionmentioning
confidence: 99%